A STUDY ON TRADITIONAL AND CULTURAL BASED OCCUPATION WITH REFERENCE TO DAIVA KOLA WITH SPECIAL REFERENCE TO DAKSHINA KANNADA DISTRICT - M, PRASHANTH; Mrs. Rekha Shetty (IJRDO - Journal of Business Management, 2019)
Tulu culture, rituals and traditions are rich and colorful. It’s a history that spirit worship have been practiced from eight centuries. Centuries old tradition from earlier Indian civilization. Daiva Kola ritual performance is the Traditional and culture based occupation or services in which the trust or faith of the people towards god especially those people who resides in Dakshina Kannada. It has come from many generations. The Daiva kola ritual performance is the caste based occupation there were people from the few caste people providing this services to entire district of Dakshina Kannada.